Agile Human Resource Management Adaptation and Local Culture in Multinational Companies - Sangkota, Megawaty; Idris, Idris; Adam, Rosida P (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Globalization and increasing workforce diversity have prompted multinational companies to adopt agile Human Resource Management (HRM) practices tailored to local cultural contexts. This study aims to examine how PT SASL and Sons Indonesia, with its multicultural workforce of expatriates and local employees, integrates agile HRM principles into the Indonesian work environment. Employing a qualitative case study approach, data were gathered through in-depth interviews with 19 expatriates, analysis of internal documents, and thematic analysis using specialized software. Findings reveal that successful adaptation depends on aligning agile values of flexibility, collaboration, and adaptability with Indonesian cultural values of cooperation, harmony, and respect for hierarchy. Cross-cultural communication emerged as a crucial factor in bridging differences in values and work styles. Managerial support, mentoring, and cross-cultural training facilitated smoother organizational acculturation. Challenges identified include gender disparities in leadership and tensions between agile work principles and existing bureaucratic structures. The study concludes that agile HRM can be effectively implemented in multinational settings when adapted to local cultural norms. It offers theoretical contributions to adaptive HRM frameworks and provides practical insights for building inclusive, responsive organizations that can navigate cultural diversity while maintaining operational agility.